Dinámica vegetal de la pradera-tamarizal en el Galacho de Juslibol (Zaragoza) - Ibarra, Paloma; Barrón, Gustavo; Longares, Luis Alberto; Pérez, Fernando; Sesé, Pedro (Geographicalia, 2017)
This paper presents a diagnosis about vegetation dynamics of a mosaic of botanical communities named "prairie-scrub of Tamarix gallica" and placed at the NW sector of the "Galacho de Juslibol" (Valle del Ebro, Zaragoza).